NILAI-NILAI BUDAYA DALAM ANTOLOGI KUNANG-KUNANG CERITA RAKYAT SELAKAU TIMUR - Krismonikasari Winarsih; Totok Priyadi; Agus Wartiningsih (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThis study aims to determine the cultural value contained in the anthology of East Selakau folklore. The research method used is descriptive with a qualitatives research from. The data source of this research is a document in the form of an anthology book Kunang-Kunang folklore of East Selakau and the data is a cultural value that is reflected in qoutes in the form of words, phrases or sentences. The results of the study show that cultural values describe the relationship between humans and religious systems, namely believing in God, believing in ghosts, and namely believing in the unseen. Cultural values that describe the relatonship between humans and social system, namely deliberation to reach consensus and mutual cooperation. Cultural values that describe the relationship between humans and their means of life, namely food equipment for human life and equipment for human life.cultural values that describe the relatonship between humans and themselves are emotional, strong-willed, and diligent.   Keywords: Anthologies, Cultural values, Selakau East.